The Quantum Pair of Pants - Klimek, S.; Mcbride, M.; Rathnayake, S.; Sakai, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We compute the spectrum of the operator of multiplication by the complex coordinate in a Hilbert space of holomorphic functions on a disk with two circular holes. Additionally we determine the structure of the C∗-algebra generated by that operator. The algebra can be considered as the quantum pair of pants.